Non‐invasive depth profiling by space and time‐resolved Raman spectroscopy. (22nd May 2013) - Sundarajoo, Shankaran; Izake, Emad L.; Olds, William; Cletus, Biju; Jaatinen, Esa; Fredericks, Peter M.
Abstract : Time‐resolved Raman spectroscopy, spatially offset Raman spectroscopy and time‐resolved spatially offset Raman spectroscopy (TR‐SORS) have proven their capability for the non‐invasive profiling of deep layers of a sample. Recent studies have indicated that TR‐SORS exhibits an enhanced selectivity toward the deep layers of a sample. However, the enhanced depth profiling efficiency of TR‐SORS, in comparison with time‐resolved Raman spectroscopy and spatially offset Raman spectroscopy, is yet to be assessed and explained in accordance to the synergistic effects of spatial and temporal resolutions. This study provides a critical investigation of the depth profiling efficiency of the three deep Raman techniques. The study compares the efficiency of the various deep Raman spectroscopy techniques for the stand‐off detection of explosive precursors hidden in highly fluorescing packaging. The study explains for the first time the synergistic effects of spatial and temporal resolutions in the deep Raman techniques and their impact on the acquired spectral data. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Time‐resolved Raman spectroscopy, spatially offset Raman spectroscopy and time‐resolved spatially offset Raman spectroscopy are critically investigated for their selectivity toward the deep layers of a sample and their efficiency in the stand‐off detection of explosive precursors hidden in highly fluorescing packaging.